Driving an Oxidative Phenotype Protects Myh4 Null Mice From Myofiber Loss During Postnatal Growth - Zeng, Caiyun; Shi, Hao; Kirkpatrick, Laila T.; Ricome, Aymeric; Park, Sungkwon; Scheffler, Jason M.; Hannon, Kevin M.; Grant, Alan L.; Gerrard, David E. (Frontiers in Physiology, 2022)
Postnatal muscle growth is accompanied by increases in fast fiber type compositions and hypertrophy, raising the possibility that a slow to fast transition may be partially requisite for increases in muscle mass. To test this hypothesis, we ablated the Myh4 gene, and thus myosin heavy chain IIB protein and corresponding fibers in mice, and examined its consequences on postnatal muscle growth. Wild-type and Myh4-/- mice had the same number of muscle fibers at 2 weeks postnatal. However, the gastrocnemius muscle lost up to 50% of its fibers between 2 and 4 weeks of age, though stabilizing thereafter. To compensate for the lack of functional IIB fibers, type I, IIA, and IIX(D) fibers increased in prevalence and size. To address whether slowing the slow-to-fast fiber transition process would rescue fiber loss in Myh4-/- mice, we stimulated the oxidative program in muscle of Myh4-/- mice either by overexpression of PGC-1α, a well-established model for fast-to-slow fiber transition, or by feeding mice AICAR, a potent AMP kinase agonist. Forcing an oxidative metabolism in muscle only partially protected the gastrocnemius muscle from loss of fibers in Myh4-/- mice. To explore whether traditional means of stimulating muscle hypertrophy could overcome the muscling deficits in postnatal Myh4-/- mice, myostatin null mice were bred with Myh4-/- mice, or Myh4-/- mice were fed the growth promotant clenbuterol. Interestingly, both genetic and pharmacological stimulations had little impact on mice lacking a functional Myh4 gene and suggesting Myh4-/- muscle was incapable of facilitating hypertrophy and argues an intact fast-twitch muscle fiber type program is obligatory for maximal muscle hypertrophy. Curiously, however, cell signaling events responsible for IIB fiber formation remained intact in the tissue. These findings further show disrupting the slow-to-fast transition of muscle fibers compromises muscle growth postnatally and suggest that type IIB myosin heavy chain expression and its corresponding fiber type may be necessary for fiber maintenance, transition and hypertrophy in mice. The fact that forcing muscle metabolism toward a more oxidative phenotype only partially compensates for the lack of the Myh4 gene provides new avenues for attenuating the loss of fast-twitch fibers in aged or diseased muscles.